PENINGKATAN KUALITAS DAN PRODUKTIVITAS SANTAN KELAPA PADA KELOMPOK USAHA PERAJIN KELAPA - Ulfi Pristiana; Cholis Hidayati; Adiati Trihastuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Community Service Activities is the implementation of IbM program in 2016 conducted by coconut seller business group in Tambak Rejo Waru Sidoarjo village.So far, the efforts made by these partners have been good but this condition still cannot be said optimally because the process used is still manually so that themanufacturing process takes a long time and the processing becomes less efficient.The purpose of this program is to help coconut business groups to develop theirbusiness with the help of coconut squeezer which is expected to improve the qualityand productivity of the business. The method is done by conditioning the situation with the condition of theobject. With the implementation of this program is divided into 2 parts of theimplementation of the activities of management training and the provision ofassistance of a squeeze tool of coconut and frezeer. Training is done in the field ofmanagement, namely finance, marketing and entrepreneurship and production. Theprovision of tools is intended to assist partners in improving quality and productivityand is expected to improve business profitability.